Ureditev bivalnega okolja pri astmatikih in pogostnost astmatičnih napadov - Jukić Petrovčič, Jasna (Obzornik zdravstvene nege, 1998)
Asthma is the most frequent chronic disease in childhood. Zasavje is the area with the highest air pollution in Slovenia, and lung diseases in children are frequent. Correlation between the arrangement of living environment and frequency of asthma attacks was studied. In the inquiry, 42 asthma patients aged 0 to 19, and their parents were tested. It was found out that the correlation between handling of asthma patients and their parents about the arrangement of living environment and frequency of asthma attacks (r = 0.065; p < 0.001), especially about sorts of the floor (p < 0.05), curtains material (p < 0.005), room furniture (p < 0.01) and cigarette's smoke in it (p < 0.05).
Keywords: Asthma; astma; bivalno okolje; bolezni dihal; Child; Environmental exposure; Etiology; Housing; kronične bolezni; Questionnaires